The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VII. Description of Madastiger robustus gen. and sp. nov. from Central Madagascar - Hlaváč, Peter; Baňař, Petr (Zootaxa, 2017)
Madastiger robustus, gen. and sp. nov., is described based on a single male collected by sifting of leaf-litter in Ambohitantely Special Reserve, Central Madagascar. The aedeagus has apical accessory lobes, a unique feature within the tribe Clavigerini, which are here described and illustrated. The genus is tentatively assigned to the subtribe Mastigerina (Pselaphinae: Clavigeritae: Clavigerini).